Upaya Penyidik Polri Dalam Melakukan Penyitaan Terhadap Harta Benda Hasil Kejahatan Korupsi di Tinjau Menurut Undang Undang Nomor 8 Tahun 2010 Tentang Pencegahan dan Pemberantasan Tindak Pidana Pencucian Uang (Studi di Polda Aceh) - Akmaluddin, Akmaluddin (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2022)
Corruption in Indonesia is increasingly happening and has an impact on the people. The people must bear the consequences of corruption. The impoverishment of corruptors is considered a new breakthrough in cracking down on cases of corruption. The concept of impoverishment of corruptors can be carried out by confiscation of assets resulting from criminal acts of corruption and compensation for losses caused by criminal acts of corruption. The concept of impoverishment of corruptors is considered capable of providing a deterrent effect as well as a form of reducing corruption.The impoverishment of corruptors in Indonesia has not been implemented explicitly. The implementation of criminal sanctions for impoverishing corruptors is only by confiscation of assets resulting from criminal acts of corruption, the amount of which is adjusted to the state's financial losses. This cannot be said to impoverish corruptors because only assets originating from criminal acts of corruption are confiscated and not necessarily the corruptors will become poor. The impoverishment of corruptors is carried out by confiscation of all objects that are the result of a criminal act of corruption and/or by payment of replacement money in the amount of which is in accordance with the state financial losses taken and arising from corruption. The impoverishment of corruptors has not become a legal breakthrough for law       enforcement in Indonesia in eradicating corruption.Law enforcement officials in eradicating money laundering are still lacking experience in implementing the law, in other words, they lack a broad and in-depth understanding of Number 25 of 2003 concerning the crime of money laundering, especially the provisions regarding the confidentiality of witnesses/reporters and proof of money laundering cases in relation to money laundering. predicate offense (original crime).There needs to be a reconceptualization of the concept of impoverishment of corruptors. Reconceptualization by providing clear directions for law enforcement regarding the concept of impoverishment of corruptors, so that the implementation of impoverishment of corruptors can be carried out as a legal breakthrough that provides a deterrent effect in corruption. Keywords: Crime, Corruption, Money Laundring,